“I did It Merely for Taking Photos and Seizing Unlimited Freedom”: The Ideology of Rooftoppers - Yusuf Kurniawan; Mugijatna Mugijatna; Warto Warto; Wakit Abdullah Rais (Universitas Sebelas Maret, 2022)
Recently, rooftopping actions got more and more thrilling and undoubtedly could jeopardize the rooftoppers. This could not hardly be understood as a mere hobby since they had (intentionally) put their lives at risk of death. Thus, this article examines the ideology of rooftoppers making them insist on doing rooftopping although some of them underwent severe punishment and bad experience. Fifteen Indonesian rooftoppers were shortlisted by using ethnographic approach and snowball sampling technique. In addition, six foreign rooftoppers were approached using netnography. Hermeneutics was utilized to analyze the data, comprising of in-depth interview with the informants and their pictures and videos obtained from either the informants directly or their Instagram accounts. Both Indonesian and foreign rooftoppers showed their persistence and perseverance in their rooftopping performance. They shared similar ultimate goals, namely taking hard-to-replicate pictures and seizing unlimited freedom at the rooftop.